STRATEGY FOR BUSINESS PORTFOLIO DEVELOPMENT OF PT SEKAR LAUT, TBK. - Homisah Homisah; Idqan Fahmi; Ahmad Mukhlis Yusuf (School of Business, IPB University (SB-IPB), 2016)
PT Sekar Laut, Tbk. (PTSL), as a local company, has three main business units including snack crackers, cooking spices and private label. Due to the potentials of Indonesia, it is expected that PTSL can upscale its competitive advantage and has an ability to compete with global companies as well. The objectives of this research were 1) analyzing relative positioning of PTSL compared with market leaders in snack and cooking spices industries, 2) analyzing Life Cycle phase per business unit, 3) analyzing positioning of each product category in portfolio matrix, 4) formulating strategic recommendations to the management for each product category of PTSL. The method used in this study was descriptive analysis. The analysis tools used in this study were BCG matrix, Life Cycle model, IFE, IFI and GE matrix. The results showed that relative positioning of crackers and cooking spices business units in BCG matrix is in Question Marks quadrant. The results of Life Cycle model for snack crackers, cooking spices, and private label showed that they are in Growth phase. The result of portfolio analysis by GE matrix showed that shrimp cracker and fish cracker product categories are in Selective Growth quadrant. Vegetables cracker, cooking spices, uleg chili sauce, burger buns are in Investment and Growth quadrant. The strategic recommendation for shrimp and fish crackers is to identify the growth segment, aggressive investment and uphold position. The strategic recommendations for vegetable cracker, cooking spices, uleg chili sauce, and burger buns are growth, seeking for dominance and maximum investment.Keywords: portfolio analyzing, crackers, cooking spices, uleg chili sauce, burger buns